I Spy A (Not So) White Lie - McCombie, Karen; Monks, Lydia (London : Walker Books, 2009)
At first, new girl April is well liked by Indie and her two best friends, Soph and Fee, especially when she has exciting stories to tell. But April's tall tales grow more extraordinary and eventually seem designed to split Indie away from the otherwise inseparable best friends. Indie is not to be discouraged, though, and with the help of babysitter Caitlin, the three friends come to realize the truth about April's fibs - and help her out!
3-6.